Graph machine learning : take graph data to the next level by applying machine learning techniques and algorithms /: take graph data to the next level by applying machine learning techniques and algorithms. (2021) - Stamile, Claudio; Marzullo, Aldo; Deusebio, Enrico
No abstract available